Pengaruh Penerapan Biaya Lingkungan Terhadap ROA, ROE, Dan NPM Di PT Aneka Tambang Tbk - Fillah Ardhi Fadhillah; Maria Yovita R. Pandin (Universitas 45 Surabaya, 2024)
Environmental damage caused by mining activities by PT ANTAM tbk is an ongoing problem. That continues to be an ongoing problem. This research seeks to provide information about the effect of environmental costs on company profitability for prospective stockholders or shareholders of ANTAM companies. The data used in the following research The following research uses a quantitative method in which the data is obtained from ANTAM tbk annual report in the period 2019-2023.